Acquired methemoglobinemia presenting to the pediatric emergency department: a clinical challenge. Issue 5 (September 2020) - Friedman, Nir; Scolnik, Dennis; McMurray, Lindsey; Bryan, Jennifer
ABSTRACT: Objectives: Acquired methemoglobinemia (MetHb) is an uncommon presentation of cyanosis in the pediatric emergency department (ED), making its diagnosis and management a clinical challenge. Through this case series we hope to improve clinician ability to recognize the potential for MetHb in pediatric ED patients and to avoid overlooking this important cause of cyanosis. Methods: This was a case series using a health records review, investigating patients diagnosed with MetHb at our pediatric ED during 2007–2018. We included only cases with methemoglobin saturation ≥5%. Results: Ten patients were diagnosed with MetHb in our pediatric ED during the study period. Five had an underlying hematologic disease who received a pharmacologic trigger known to induce MetHb as well (four dapsone, one rasburicase). The other five patients were previously healthy, who presented with a clinical picture of hemolytic anemia, all of whom were diagnosed with previously unknown glucose-6-phosphate dehydrogenase (G6PD) deficiency. Two of the patients received methylene blue, and five patients needed packed red blood cells. All of the patients survived the acute MetHb episode. Conclusion: Acquired MetHb in the pediatric ED is a rare but important cause of cyanosis. Diagnosis and management of acute, acquired MetHb in the ED requires a high level of suspicion, and a background knowledge of the common precipitants and underlying conditions associated with this condition. We hope this case series will help ED physicians to consider MetHb in pediatric patients presenting with cyanosis and persistent hypoxia. Exposure to known precipitants (e.g., medications and foods), particularly in the setting of active treatment for malignancy or with symptoms of hemolytic anemia should further increase suspicion.